H-Infinity Loop-Shaping Controller for Load Frequency Control of a Deregulated Power System. (2016) - Davidson, R. Arlene; Ushakumari, S.
Abstract: Load frequency control is an essential component of Automatic Generation Control of power systems. Deregulated power system isa highly complex and uncertain system because of multiple bilateral transactions taking place. This necessitates the use of advanced robust controllers for load frequency control. A decentralized load frequency controller using H-infinity based loop-shaping method is suggested for a two area deregulated non-reheat thermal power system in this paper. The connections between each control area with the rest of the system as well as the contracts existing in a deregulated system are treated as input disturbance signals to achieve decentralization. Dynamic responses for three contract cases of operation in a deregulated system using the H-infinity controller are obtained.